Development Of Material On Creed And Morality Based On The Values Of Religious Moderation In The Material On Ethics In Social Media - Puteri Amelia Rosanti; Muhammad Noor Alamsyah; Mardhiya Agustina (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2026)
This study aims to develop Akidah Akhlak learning materials based on religious moderation values on the topic of social media etiquette for Grade VIII students of Madrasah Tsanawiyah. The study employed the Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The developed products included learning modules, learning videos, student worksheets (LKPD), and assessment instruments integrating the values of tolerance, national commitment, non-violence, and accommodation of local culture. The research subjects were Grade VIII students of MTsN 1 Hulu Sungai Selatan. The results showed that the developed product achieved a validity score of 82.19%, categorized as very feasible. Practicality testing indicated positive results, with student activity reaching 88.60% and student responses reaching 87.80%, both categorized as very good. The effectiveness test demonstrated an increase in learning outcomes from a pretest score of 65.20 to a posttest score of 85.60, with an N-Gain score of 0.59 in the moderate category. These findings indicate that the developed materials effectively improved students’ understanding and application of Islamic social media etiquette. The novelty of this study lies in integrating religious moderation values into a comprehensive Akidah Akhlak learning package focused on social media etiquette. The developed product is considered feasible, practical, and moderately effective, contributing to Islamic education by strengthening students’ digital character, tolerance, responsibility, and awareness of ethical behavior in digital environments.